Whole Genome Sequencing of Enteroviruses Species A to D by High-Throughput Sequencing: Application for Viral Mixtures - Joffret, Marie-Line; Polston, Patsy M.; Razafindratsimandresy, Richter; Bessaud, Maël; Heraud, Jean-Michel; Delpeyroux, Francis (Frontiers in Microbiology, 2018)
Human enteroviruses (EV) consist of more than 100 serotypes classified within four species for enteroviruses (EV-A to -D) and three species for rhinoviruses, which have been implicated in a variety of human illnesses. Being able to simultaneously amplify the whole genome and identify enteroviruses in samples is important for studying the viral diversity in different geographical regions and populations. It also provides knowledge about the evolution of these viruses. Therefore, we developed a rapid, sensitive method to detect and genetically classify all human enteroviruses in mixtures. Strains of EV-A (15), EV-B (40), EV-C (20), and EV-D (2) viruses were used in addition to 20 supernatants from RD cells infected with stool extracts or sewage concentrates. Two overlapping fragments were produced using a newly designed degenerated primer targeting the conserved CRE region for enteroviruses A-D and one degenerated primer set designed to specifically target the conserved region for each enterovirus species (EV-A to -D). This method was capable of sequencing the full genome for all viruses except two, for which nearly 90% of the genome was sequenced. This method also demonstrated the ability to discriminate, in both spiked and unspiked mixtures, the different enterovirus types present.